Carbon conduction effect and multi-scenario carbon emission responses of land use patterns transfer: a case study of the Baiyangdian basin in China - Gao, Xing; Zhao, Meiran; Zhang, Mengmeng; Guo, Zhongyuan; Liu, Xiao; Yuan, Zihua (Frontiers in Environmental Science, 2024)
Carbon pooling and release occur all the time in all corners of the earth, where the land use factor is key to influencing the realization of carbon peaking and neutrality. Land use patterns and carbon emissions change under different scenarios and analyzing the correlation will help formulate scientific land use policies for the future. In this study, through remote sensing data, we investigated the changes in land use patterns and carbon emissions in the Baiyangdian basin in China from 2000 to 2020 and analyzed the carbon conduction effect with the help of a land transfer matrix. The geographical simulation and optimization system-future land use simulation (GeoSOS-FLUS) and Markov models were used to predict the land use changes and carbon emissions under the four different scenarios for the region in 2035. The results indicated that (i) the net land use carbon emissions increased from 52,163.03 × 103 to 260,754.91.28 × 103 t from 2000 to 2020, and the carbon source-sink ratio exhibited a general uptrend; (ii) the net carbon emissions due to terrestrial transfers increased over time. The carbon conduction effects due to the transfer of forests, grasslands, water areas, and unused lands to built-up lands also showed a rising trend, albeit the latter two exhibited only small changes; (iii) in 2035, the net carbon uptake under the four development scenarios was predicted to be 404,238.04 × 103, 402,009.45 × 103, 404,231.64 × 103, and 404202.87×103 t, respectively, with all values much higher than that of the study area in 2020. The maximum carbon sink capacity was 817.88 × 103 t under the double-carbon target scenario, and the maximum carbon source emission was 405,033.61 × 103 t under the natural development scenario. The above results provide an essential reference for low carbon-based urban land use regulations for the Baiyangdian basin and other similar projects in the future.